The association between chronological age, skeletal maturity and dental maturity - Cutajar Brenda Lee; McDonald Fraser; Roberts Graham; Lucas Victoria; Camilleri Simon (Sciendo, 2019)
The aim of this study was to analyse the correlation between skeletal and dental maturity.